The Czech and Slovak Experience
XIV, 235 p.
Keywords: The Czech and Slovak Experience assembles essays by leading specialists from the USA, Canada, Britain and Czechoslovakia on key aspects of modern Czech and Slovak history: Joseph II's contribution to the development of the Czech national movement, the troubled relationship between Czechs and Slovaks as seen through Czech and Slovak eyes, Slovak linguistic separatism, the emergence of political democracy in post-Versailles Czechoslovakia, Masaryk as a religious heretic, Czechoslovakia's Germans and their treatment by the Czechoslovak government, and Prague's Jewish community after 1918.